Aazheyaadizi : worldview, language and the logics of decolonization - Freeland, Mark D. (American Indian studies series., 2021)
"A study for students of Indigenous and linguistic disciplines that demonstrates the significant relationship between a clearly defined theory of worldview and the logics of decolonization for Indigenous thought and praxis"--